ESTRUTURA DA ASSEMBLEIA DE SCOLYTINAE (COLEOPTERA: CURCULIONIDAE) EM ÁREAS FLORESTADAS COM Eucalyptus spp. NO SUL DO RIO GRANDE DO SUL - Wollmann, Jutiane; Garcia, Mauro Silveira; Flechtmann, Carlos Alberto Hector; Finkenauer, Elder; Garcia, Flávio Roberto Mello (Universidade Federal de Santa Maria, 2017)
ABSTRACT The aim of this study was to contribute to the knowledge of the assembly of Scolytinae beetles associated with Eucalyptus plantations in southern Rio Grande do Sul state, Brazil, and determine species of importance to the culture. Biweekly samples were taken from five Fibria Celulose S/A farms forested with Eucalyptus spp., from February 2006 to December 2010, with flight intercept traps baited with 95% ethanol. We collected 7,365 specimens within 76 species, 18 genera, and seven tribes. Corthylini, represented by the genera Corthylus, Monarthum, Amphicranus, Metacorthylus, Microcorthylusand Tricolus, and Xyleborini, by Ambrosiodmus, Dryocoetoides, Xyleborinus, Xyleborus and Xylosandrus, were the most representative tribes, with 42.1% and 31.6% species, respectively. Xylosandrus retusus (Eichhoff) and Xyleborinus saxeseni (Ratzeburg) were the most abundant species, with 52.64% and 27.98% of all specimens sampled, followed by Corthylus antennarius Schedl with 4.15% beetles collected. Fifteen species were common to all sites, including Xyleborus ferrugineus (Fabricius), considered a potential pest to the culture, while 25 species were found exclusively in only one site. The farm Cerro Alegre had the highest species richness and larger number of exclusive species; São Manoel farm presented the highest diversity index and equitability; Aroeira farm had the highest frequency of Scolytinae and São Francisco farm showed the greatest abundance and dominance. The study of Scolytinae assemblages showed the predominance of Xylosandrus retusus and Xyleborinus saxeseni in all studied environmentals.

RESUMO O objetivo deste trabalho foi contribuir para o conhecimento da assembleia de besouros Scolytinae associada a plantios de eucalipto no sul do Estado do Rio Grande do Sul, Brasil e determinar espécies de importância à cultura. Amostras quinzenais foram retiradas de cinco fazendas da Fibria Celulose S/A, florestadas com Eucalyptus spp., no período de fevereiro de 2006 a dezembro de 2010, com armadilhas de interceptação de voo iscadas com etanol a 95%. Foram coletados 7.365 exemplares em 76 espécies, 18 gêneros e sete tribos. Corthylini, representada pelos gêneros Corthylus, Monarthum, Amphicranus, Metacorthylus, Microcorthylus e Tricolus e Xyleborini, por Ambrosiodmus, Dryocoetoides, Xyleborinus, Xyleborus e Xylosandrus foram as tribos mais representativas, com 42,1% e 31,6% espécies, respectivamente. Xylosandrus retusus e Xyleborinus saxeseni foram as espécies mais abundantes com 52,64% e 27,98% do total de espécimes amostradas, seguida por Corthylus antennarius, com 4,15% besouros coletados. Quinze espécies foram comuns a todos os locais, incluindo Xyleborus ferrugineus, considerada praga desta cultura, enquanto 25 espécies foram encontradas exclusivamente em apenas um local. A fazenda Cerro Alegre apresentou a maior riqueza de espécies e maior quantidade de espécies exclusivas; São Manoel demonstrou o maior índice de diversidade e equitabilidade; Aroeira teve a maior frequência de Scolytinae e São Francisco evidenciou a maior abundância e dominância. O estudo das assembleias de Scolytinae evidenciou o predomínio das espécies Xylosandrus retusus e Xyleborinus saxeseni em todos os ambientes estudados.
SCOLYTINAE ASSEMBLAGE STRUCTURE (COLEOPTERA: CURCULIONIDAE) IN FORESTED AREAS WITH Eucalyptus spp. IN SOUTHERN RIO GRANDE DO SUL STATE
Keywords: ambrosia beetles; faunistic analysis; diversity; eucalypt; besouros-da-ambrosia; análise faunística; diversidade; eucalipto